A Report of a Case With Pediatric Ovarian Steroid Cell Tumor, Not Otherwise Specified, Found With Precocious Puberty. Issue 4 (7th May 2023) - Umeda, Satoshi; Takase, Koki; Takayama, Keita; Yamamichi, Taku; Higuchi, Kohei; Kawai, Masanobu; Takeuchi, Makoto; Inoue, Masami; Usui, Noriaki
Abstract : A 4-year-old girl was admitted to our hospital because of precocious puberty. Radiologic findings revealed a fist-sized solid tumor in the left ovary without ascites, peritoneal dissemination, and distant metastasis. The patient underwent left salpingo-oophorectomy without spillage. The size of the excised tumor was 10.0×9.0×4.8 cm. On pathologic examination, the tumor was diagnosed as an ovarian steroid cell tumor, not otherwise specified. In the present case, although the diameter of the tumor (>7 cm) and three mitoses per 10 high-power fields represented some potential for malignancy, we opted for careful observation without chemotherapy as the tumor was of clinical stage Ia.